Towards a generative software development approach for rapid prototyping iDTV applications - Kulesza, Raoni; Meira, Silvio Romero de Lemos; Ferreira, Thales Pordeus; Neto, Vicente Ramos Silva; Alexandre, Eduardo Freire de Santana; Souza Filho, Guido Lemos de (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
This paper presents an approach for development Interactive Digital TV applications. Methodology seeks to explore concepts and techniques already established in the area of generative software development for rapid prototyping application source code from models. The main goal is to define a systematic method using notations of high level and platform-independent to allow integration of media objects and complex application logic in applications, for example the use of Web Services. In addition, the proposed solution takes care of generating a source compatible with existing authoring tools to allow a subsequent spatial and temporal design of applications. The work also describes a case study for iTV domain for illustration purpose and an experimental pilot study to evaluate the impact of the approach usage.